2019
DOI: 10.1302/2058-5241.4.180088
|View full text |Cite
|
Sign up to set email alerts
|

The current role of robotics in total hip arthroplasty

Abstract: Robotic total hip arthroplasty (THA) improves accuracy in achieving the planned acetabular cup positioning compared to conventional manual THA. Robotic THA improves precision and reduces outliers in restoring the planned centre of hip rotation compared to conventional manual THA. Improved accuracy in restoring hip biomechanics and acetabular cup positioning in robotic THA have not translated to any differences in early functional outcomes, correction of leg-length discrepancy, or postoperative complications co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 41 publications
(53 reference statements)
1
38
0
1
Order By: Relevance
“… 11 14 Robotic-assisted orthopaedic surgery has the potential to improve the accuracy of component positioning in THA, thus, enhancing clinical outcomes. 15 , 16 This review aims to summarize the history and development of robotic technology in orthopaedic surgery, and discuss the evidence base surrounding its use.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 11 14 Robotic-assisted orthopaedic surgery has the potential to improve the accuracy of component positioning in THA, thus, enhancing clinical outcomes. 15 , 16 This review aims to summarize the history and development of robotic technology in orthopaedic surgery, and discuss the evidence base surrounding its use.…”
Section: Introductionmentioning
confidence: 99%
“…An instant shut-off switch was available to the surgeon if required. 15 In recent years, semi-active robotic systems have become increasingly popular. 15 , 20 These systems require the surgeon to guide the robotic arm for bony preparation via a haptic feedback mechanism that ensures minimal deviation from the pre-determined surgical plan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, with the introduction of semi‐active, haptic robotic systems, there has been renewed interest in robotic devices for THA 2,3 . In semi‐active robot‐assisted THA, the acetabular preparation and implantation are performed with the assistance of a robotic arm.…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies have shown no difference in CO THA versus RO THA with respect to functional outcomes, implant survivorship, and complications at short-term follow-up [4,17,19,21]. Delays in the widespread implementation of RO THA have been attributed to the limited data showing any functional benefit with this procedure compared to an already established and highly cost-effective CO THA [7,13].…”
Section: Introductionmentioning
confidence: 99%